Innovative Linguodidactic Methods for Developing Students’ Pragmatic Competence - Rustamova Feruzabonu Ilkhomovna (International Journal on Integrated Education, 2026)
This article presents a scientific and theoretical analysis of methods aimed at developing pragmatic competence in students of foreign language philology. It is grounded in Noam Chomsky’s theory of linguistic competence, the communicative competence model developed by Michael Canale and Merrill Swain, as well as J.L. Austin’s speech act theory. Additionally, the didactic features of methods such as task-based learning, role play, case studies, project-based learning, the use of authentic materials, and digital simulations, as well as the skills they develop and their role in education, are examined in accordance with the requirements of CEFR standards and UNESCO strategies. Furthermore, it is demonstrated that applying these methods as an integrated and complementary system contributes to the comprehensive development of students’ communicative competence.